Combination of biocompatible hydrogel precursors to apatitic calcium phosphate cements (CPCs): Influence of the in situ hydrogel reticulation on the CPC properties. Issue 1 (23rd July 2020) - Ramirez Caballero, Silvia Stella; Ferri‐Angulo, Daniel; Debret, Romain; Granier, Fabien; Marie, Sébastien; Lefèvre, François‐Xavier; Bouler, Jean‐Michel; Despas, Christelle; Sohier, Jérôme; Bujoli, Bruno
Abstract: In the field of bone regenerative medicine, injectable calcium phosphate cements (CPCs) are used for decades in clinics, as bone void fillers. Most often preformed polymers (e.g., hyaluronic acid, collagen, chitosan, cellulose ethers…) are introduced in the CPC formulation to make it injectable and improve its cohesion. Once the cement has hardened, the polymer is simply trapped in the CPC structure and no organic subnetwork is present. By contrast, in this work a CPC was combined with organic monomers that reticulated in situ so that a continuous biocompatible 3D polymeric subnetwork was formed in the CPC microstructure, resulting in a higher permeability of the CPC, which might allow to accelerate its in vivo degradation. Two options were investigated depending on whether the polymer was formed before the apatitic inorganic network or concomitantly. In the former case, conditions were found to reach a suitable rheology for easy injection of the composite. In addition, the in situ formed polymer was shown to strongly affect the size, density, and arrangement of the apatite crystals formed during the setting reaction, thereby offering an original route to modulate the microstructure and porosity of apatitic cements.